RELATIONSHIPS AMONG PRODUCT QUALITY, SERVICE QUALITY, AND CUSTOMER SATISFACTION TOWARDS AMAL BANK IN - Elmi, Mahad Arte; HARUN, AMRAN (Research in Management of Technology and Business, 2023)
The Amal Bank, which operates in Somalia, is up against many problems due to the increased competition among other financial institutions. As a consequence, a variety of techniques have been developed in order to keep the customer, and improving both the product quality and the degree of service quality has been regarded as an essential aspect of the company's success. Thus, customer satisfaction is important to the success of every business. The standard of a bank's products and services is a big part of how well it does its performance. So, the objective of this study is to examine the relationships between product quality, service quality, and customer satisfaction at Amal bank in Mogadishu Somalia. The data was collected through a Google form questionnaire to 285 customers of Amal bank in Mogadishu areas such as Xamarjajab, Madina, and Hodan. This study used Statistical Package for Social Science (SPSS) version 23 to analyze descriptive, correlation, and regression analysis. It was found that customer satisfaction was only related to product quality and service quality (reliability, empathy, assurance) Amal bank is required to improve the quality of its products and services and to tell its customers more about itself and what it has to offer. Also, Amal bank needs to work on better its customer service, reliability, and products, as these things were found to have a strong effect on how customers satisfied.